Testing FLUKA on neutron activation of Si and Ge at nuclear research reactor using gamma spectroscopy - Bazo J. (2018)
The authors gratefully acknowledge DGI-PUCP for financial sup-port under Grants No. DGI-2015-192 and DGI-2017-3-0019, as wellas CONCYTEC under Grant No. FONDECYT-2013-102. The authorswish to thank the FLUKA scientific committee for useful commentsand suggestions, Jose Fernandes and Francisco Rumiche for the SEMmeasurements and Jorge Andrés Guerra, Patrizia Pereyra and DanielPalacios for useful discussions.